Features of temperature-dependent internal friction at phase decomposition of Nb-Ti alloy - Arzhavitin, V.M. (Functional Materials, 2008)
Experimental dependence of internal friction Q⁻¹(T) on heating temperature T of pre-strained Nb-(48.5±1,5)Ti (wt. %) alloy is a superposition of two internal friction peaks with maxima at 250°C and 300°C. It is shown by calculation that both the peaks are due to nucleation and subsequent diffusion-controlled growth of a-Ti segregates in the walls of dislocation cells. The first peak is connected with Ti diffusion in the cell boundaries while the second one, in the volumes thereof. Експериментальна залежність внутрішнього тертя Q⁻¹(1) від температури Т нагрівання попередньо деформованого сплаву складу Nb-(48,5±1,5)Ті (масс. %) являє собою суперпозицію з двох пінів внутрішнього тертя з температурами максимумів 250°С і 300°С. Розрахунковим шляхом показано, шо обідва ці піки обумовлені зародженням і наступним дифузійним ростом виділень а-Ті у стіннах дислокаціонних комірок Перший пік пов'язаний з дифузією Ті на границях, а другий - в об'ємах цих комірок. Экспериментальная зависимость внутреннего трения Q⁻¹(T) от температуры Т нагрева предварительно деформированного сплава состава Nb-(48,5±1,5)Ti (wt. %) представляет собою суперпозицию из двух пиков внутреннего трения с температурами максимумов 250°С и 300°С . Расчётным путём показано, что оба этих пика обусловлены зарождением и последующим диффузионным ростом выделений a-Ti в стенках дислокационных ячеек. Первый пик связан с диффузией Ti в границах, а второй - в объёмах этих ячеек.